2016
DOI: 10.1186/s40478-016-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of cerebral TDP-43 pathology in sporadic amyotrophic lateral sclerosis: Evidence for clinico-pathologic subtypes

Abstract: Frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS) are types of major TDP-43 (43-kDa TAR DNA-binding protein) proteinopathy. Cortical TDP-43 pathology has been analyzed in detail in cases of FTLD-TDP, but is still unclear in cases of ALS. We attempted to clarify the cortical and subcortical TDP-43 pathology in Japanese cases of sporadic ALS (n = 96) using an antibody specific to phosphorylated TDP-43 (pTDP-43). The cases were divided into two groups: those without pTDP-43-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…As recently reviewed, phosphorylation is one of the major posttranslational modifications of TDP‐43 that has been described to affect protein function both in healthy and disease conditions . Indeed, aberrant TDP‐43 phosphorylation at residues S409/410 is one of the major distinguishing features of TDP‐43 pathology . Regarding this issue, one important conclusion that can be drawn from our study is that there is no correlation between the abundance of TDP‐43 protein expression in different brain regions and the pathological S409/410 pTDP‐43 immunoreactivity.…”
Section: Discussionmentioning
confidence: 52%
“…As recently reviewed, phosphorylation is one of the major posttranslational modifications of TDP‐43 that has been described to affect protein function both in healthy and disease conditions . Indeed, aberrant TDP‐43 phosphorylation at residues S409/410 is one of the major distinguishing features of TDP‐43 pathology . Regarding this issue, one important conclusion that can be drawn from our study is that there is no correlation between the abundance of TDP‐43 protein expression in different brain regions and the pathological S409/410 pTDP‐43 immunoreactivity.…”
Section: Discussionmentioning
confidence: 52%
“…We do not believe this is the case, since only small number of dendrites have pTDP-43, and of these, only 4% also have poly-GR aggregations. Current classifications of ALS are based on TDP-43 neuropathology, and based either on morphology [6, 37, 48], or anatomy [6]. It has already been shown that occasionally TDP-43 surrounds perinuclear poly-GA aggregations [36] and there are perinuclear poly-GR and poly-PA aggregations in spinal cord that co-localized with pTDP-43 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the morphology and distribution of cortical TDP-43 pathology, FTLD cases are routinely classified into one of four pathological subtypes (FTLD-TDP Type A-D) [ 21 , 27 ], with Types A and B the most commonly identified in the ~20% of FTLD cases with ALS (FTLD-ALS) [ 8 , 17 , 22 , 27 ]. Although TDP-43 pathology is identified in the frontal cortices of ~70% of ALS cases without FTLD [ 9 ], these cases are not routinely subtyped according to the FTLD classification scheme, with a novel TDP-43 classification scheme recently proposed for ALS [ 29 ]. Given the wide acceptance of the FTLD-ALS continuum theory, it is not clear why cortical TDP-43 pathology would be classified according to two separate schemes, particularly since cortical TDP-43 pathology identified in Alzheimer’s disease cases (AD) are classified as per in FTLD [ 4 , 33 ].…”
Section: Introductionmentioning
confidence: 99%